Homes : today and tomorrow - Sherwood, Ruth F. (New York, N.Y. : Glencoe/McGraw-Hill, 1997)
A textbook examining the theory and history of house design, construction, and furnishing, as well as factors to be considered when buying a house.
Includes index.
Keywords: Design -- United States -- Juvenile literature; Interior decoration -- United States -- Juvenile literature; House buying -- United States -- Juvenile literature; Dwellings; Interior decoration; House construction; House furnishings